The prognostic role of heart rate recovery after exercise and metabolic syndrome in IgA nephropathy - Balázs Sági (BMC, 2021)
Abstract Background Cardiovascular (CV) morbidity and mortality are higher in chronic kidney disease (CKD) than in the general population. Reduced heart rate recovery (HRR) is an independent risk factor for CV disease. The aim of the study was to determine the prognostic role of HRR in a homogenous group of CKD patients. Methods One hundred and twenty-five IgA nephropathy patients (82 male, 43 female, age 54.7 ± 13 years) with CKD stage 1–4 were investigated and followed for average 70 months. We performed a graded exercise treadmill stress test. HRR was derived from the difference of the peak heart rate and the heart rate at 1 min after exercise. Patients were divided into two groups by the mean HRR value (22.9 beats/min). The composite (CV and renal) endpoints included all-cause mortality and any CV event such as stroke, myocardial infarction, revascularisation (CV) and end-stage renal disease, renal replacement therapy (renal). Results Patients with reduced HRR (< 23 bpm) had significantly more end point events (22/62 patients vs. 9/53 patients, p = 0.013) compared to the higher HRR (≥23 bpm). Of the secondary the endpoints (CV or renal separately) rate of the renal endpoint was significantly higher in the lower HRR group (p = 0.029), while there was no significant difference in the CV endpoint between the two HRR groups (p = 0.285). Independent predictors of survival were eGFR and diabetes mellitus by using Cox regression analysis. Kaplan-Meier curves showed significant differences in metabolic syndrome and non-metabolic syndrome when examined at the combined endpoints (cardiovascular and renal) or at each endpoint separately. The primary endpoint rate was increased significantly with the increased number of metabolic syndrome component (Met.sy. comp. 0 vs. Met. sy. comp. 2+, primary endpoints, p = 0.012). Conclusion Our results showed that reduced HRR measured by treadmill exercise test has a predictive value for the prognosis of IgA nephropathy. The presence of metabolic syndrome may worsen the prognosis of IgA nephropathy.